2022
DOI: 10.3390/microorganisms10071330
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics, Probiotics, and Postbiotics in the Prevention and Treatment of Anemia

Abstract: Iron deficiency anemia (IDA) is very common and affects approximately 1/3 of the world’s human population. There are strong research data that some probiotics, such as Lactobacillus acidophilus and Bifidobacterium longum improve iron absorption and influence the course of anemia. Furthermore, prebiotics, including galactooligosaccharides (GOS) and fructooligosaccharides (FOS), increase iron bioavailability and decrease its destructive effect on the intestinal microbiota. In addition, multiple postbiotics, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 82 publications
0
12
0
1
Order By: Relevance
“…It has been reported that, multiple postbiotics, which are probiotic metabolites, including vitamins, short-chain fatty acids, and tryptophan, are also involved in the regulation of intestinal absorption of iron and may improve iron content in body. 25 The present study increases the reliability of a growing number of studies conducted on the beneficial effects of synbiotic supplements on haematological parameters related to anaemia in haemodialysis patients but small size of enrolled haemodialysis patients in this study, was limitation of our study.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It has been reported that, multiple postbiotics, which are probiotic metabolites, including vitamins, short-chain fatty acids, and tryptophan, are also involved in the regulation of intestinal absorption of iron and may improve iron content in body. 25 The present study increases the reliability of a growing number of studies conducted on the beneficial effects of synbiotic supplements on haematological parameters related to anaemia in haemodialysis patients but small size of enrolled haemodialysis patients in this study, was limitation of our study.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, prebiotics, including galactooligosaccharides and fructooligosaccharides, increase iron bioavailability and decrease its destructive effect on the intestinal microbiota. It has been reported that, multiple postbiotics, which are probiotic metabolites, including vitamins, short‐chain fatty acids, and tryptophan, are also involved in the regulation of intestinal absorption of iron and may improve iron content in body 25 …”
Section: Discussionmentioning
confidence: 99%
“…The potential role of gut microbiota in treating anaemia has been widely reported 9,26 . Supplementation with the probiotic strain Lactobacillus plantarum 299v led to a clear increase in iron absorption in women 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…SCFAs are organic compounds consisting mainly of acetate, propionate and butyrate. In addition to lowering intestinal pH, they increase the bioavailability of some metals, e.g., iron [ 35 ]. Bacteroides thetaiotaomicron , responsible for the production of acetate and propionate, promotes the differentiation of goblet cells in the intestine and the expression of mucin-related genes.…”
Section: The Role Of Dietary Fiber and Short-chain Fatty Acidsmentioning
confidence: 99%
“…It was also observed that an increase in SCFAs enhances iron absorption. In infants with iron deficiency, a reduction in the abundance of butyrate-producing species such as Butyricicoccus, Roseburia and Coprococcus was shown [ 35 ].…”
Section: Micronutrients Gut Microbiome and Cancermentioning
confidence: 99%